P69 Are patients with chronic obstructive pulmonary disease receiving the best treatment for their cardiovascular risk factors?. (December 2018) - Masteva, H; Baker, EH; Burrage, DR
Abstract : Introduction and objectives: COPD patients are more likely to die from cardiovascular disease than from their lung disease. However, under diagnosis of vascular risk factors is common. The aim of this study was to evaluate prevalence and control of cardiovascular risk factors in COPD patients. Methods: This was a cross-sectional study of stable COPD outpatients (no exacerbation for >6 weeks). Prior diagnosis and treatment of hypertension, dyslipidaemia and diabetes was recorded. Participants underwent spirometry and measurement of blood pressure, fasting blood lipid profile, plasma glucose and glycated haemoglobin (HbA1c). Hypertension was defined as a blood pressure ≥140/90 mmHg; type 2 diabetes was defined as HbA1c≥48 mmol/mol or fasting plasma glucose ≥7.0 mmol/L, and need for lipid-lowering therapy was based on QRISK2 score ≥10%. Blood pressure was considered controlled if <140/90 mmHg. Hyperlipidaemia was considered controlled if non-HDL cholesterol was <2.5 mmol/L. Type 2 diabetes was considered controlled if HbA1c was <58 mmol/mol. Results: 56 participants were recruited (age 69±8 years, 36 (64%) male, 47±25 pack years, FEV1 % predicted 55±24 [means ±SD]). 45 (80%) participants had hypertension, 53 (95%) participants had a diagnosis of hyperlipidaemia or met the threshold for lipid-lowering therapy, and 6 (11%) participants had type 2 diabetes. The table 1 shows the proportion of participants with hypertension, hyperlipidaemia and type 2 diabetes who had an existing diagnosis (controlled), an existing diagnosis (uncontrolled) or a new diagnosis. Conclusions: In this study around a third of patients had undiagnosed hypertension, and a third met the threshold for requiring lipid lowering therapy. Even in patients who had existing diagnoses, the majority were uncontrolled. In view of the high burden of cardiovascular disease in COPD patients, more attention needs to be given to assessment, treatment and monitoring of cardiovascular risk.